Autologus fat grafting for mild to moderate velopharyngeal insufficiency: Our experience - Xoagus, Elizabeth Alexia (Division of Plastic and Reconstructive Surgery, 2019)
The standard surgical treatment of velopharyngeal insufficiency (VPI) includes revision palatoplasty, posterior pharyngeal flap and sphincter pharyngoplasty. These procedures are not without complication and can also be challenging to the occasional cleft surgeon. The greatest complication is iatrogenic obstructive sleep apnoea particularly in high risk patients. With the introduction of posterior pharyngeal wall augmentation, a lesser and simpler surgical procedure, various materials have been used for this purpose with limited success and significant complication rates. Augmentation of the velo-pharynx with autologous fat has been practiced for decades. Autologous fat has multiple advantages compared to other biological and synthetic materials used for augmentation of the velopharynx. Autologous fat is readily available, has low donor site morbidity, does not migrate, injects easily and is non-allergenic. The outcome of fat grafting for VPI is good and stable long term, albeit unpredictable due to the resorption of fat. The procedure may therefore need to be repeated in order to achieve the desired results. The aim of this study is to evaluate and document the outcome of autologous fat grating for the treatment of mild to moderate VPI in children at the Red Cross War Memorial Children's Hospital (RCWMCH). A retrospective folder review was conducted on 9 consecutive patients who underwent velopharygeal fat grating for the treatment of mild to moderate VPI at the RCWMCH from 2010 to 2014. All the patients had had primary palatoplasty performed previously and subsequently developed VPI. Patients were assessed pre- and postoperatively by two cleft surgeons, and an experienced speech and language therapist with the aid of laterl view videofluoroscopy (VF). Pre-operative and post-operative perceptual speech assessments were performed by a dedicated speech and language therapist. Two senior cleft surgeons performed pre-and post-operative videofluoroscopy interpretations. Eleven fat grafting procedures were performed on 9 patients and an average of 5.64 ml (range 1 ml to 7 ml) of autologous fat was transferred to the velopharynx. The average age at the time of operation was 6.5 years (range 3 years to 14 years) with a follow-up period of 18 months (range 7 months to 34 months). Most of the patients (7 out of 9) showed improved speech following fat grafting. There were no complications related to the fat grafting procedure. This small study suggests that fat grafting is an effective, minimally invasive surgical alternative for the treatment of mild to moderate VPI and to our knowledge, is the first reported study from Africa.